Islam, sains, dan teknologi : menggagas bangunan keilmuan fakultas sains dan teknologi Islami masa depan - Turmudi (UIN Press, 2006)
On Islam, science, and technology and their influence on study and teaching in the Dept. of Science and Technology of Islamic universities in Indonesia.